The phytoactive constituents of Eugenia selloi B.D. Jacks (pitangatuba): Toxicity and elucidation of their anti-inflammatory mechanism(s) of action - Goldoni Lazarini, Josy (2022)
We determined the phytochemical composition, anti-inflammatory mechanism of action, ROS/RNS scavenging capacity and systemic toxicity of a purified subfraction (S8) of Eugenia selloi. The composition of S8 was assessed by LC-ESI-QTOF-MS; the anti-inflammatory activity in RAW264.7 macrophages through NF-κB activation and biomarkers by multiplex in THP-1 cells; neutrophil migration, intravital microscopy and ICAM-1 expression in mice; NETs formation and CD11b expression; S8 scavenging capacity of ROS/RNS; toxicity in Galleria mellonella larvae model. Coumaric acid, quercetrin and vanillic acid were identified. S8 decreased NF-κB activation, IL-1β, IL-6, IL-10, MDC and MCP-1 levels, reduced neutrophil migration and ICAM-1 expression in mice; S8 did not interfere NET formation and CD11b expression, exhibited high antioxidant and showed negligible toxicity. E. selloi proved to be a promising, yet underexplored source of bioactive compounds, which can be useful employed in agribusiness and in the pharmaceutical and food industry to develop new products or human health supplies.